CMLHS luncheon at Bukit Gambang Resort - Ahmad, Ibrahim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
19 January 2012. The Welfare Unit of CMLHS (UNIK) was really creative. Instead of having the event at night, this year, all CMLHS members were treated with a luncheon at Bukit Gambang Resort. Clad in batik and sitting in a very relaxed mood made everyone enjoyed themselves. UNIK was generous too when everyone was presented goodie bag with a lovely mug and Gambang Theme Park voucher inside.